ZINC DIPEPTIDE COMPLEX ([ZN(II)-GLY-TYR]+)–NINHYDRIN REACTION IN PRESENCE OF GEMINI SURFACTANTS: A KINETIC STUDY - Akram, Mohd.; Kumar, Dileep; Din, Kabir-ud- (European Scientific Journal, ESJ, 2013)
Kinetics of the title reaction has been carried out by studying the reaction spectrophotometrically at 80 ºC and pH 5.0 in presence of cationic gemini (alkanediyl-α, ω- bis(dimethylhexadecylammonium bromide)) surfactants. The reaction followed first-order kinetics in [Zn(II)-Gly-Tyr]T + complex and fractional-order kinetics in [ninhydrin]T. Typical rate constant (kΨ) increase and leveling-off regions (like conventional monomeric surfactants, e.g., CTAB) are found with gemini surfactants. Additionally, the gemini surfactants also produced a third region of increasing kΨ at higher concentrations. The data are interpreted in terms of pseudo-phase model (assuming the association/incorporation of both the reactants at the micellar surface).